Peningkatan Gerak Geri Komi Melalui Gaya Melatih Secara Otoriter Dalam Bela Diri Kempo Dojo Persatuan Guru 1945 Kupang - Carles Nyoman Wali; Widiyanto Widiyanto (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
This study aims to find out the improvement of “geri komi” movement technique training on kenzhi, through the authoritative training style on kenzhi kyu IV (white belt) and kenzhi kyu III (green belt) on the dojo of Teachers Association 1945 Kupang. The sample in this study consisted of kenzhis numbering to 10, with the composition of 5 kenzhis of kyu IV (white belts) and 5 kenzhis of kyu III (green belts) which were given actions of an authoritative training style. The method used in this research is descriptive qualitative research. Data analysis was performed by a descriptive qualitative method. The results of the study conclude: (1) before applying the authoritative training style by the trainers to the kenzhis, the kenzhis were not good at making “geri komi” kick movements and did not have any improving changes in “geri komi” kick technique, but after an authoritative training style being given to the kenzhis, then there was an improvement in “geri komi” kick technique in terms of speed, accuracy, and strength. Based on the descriptive results of data analysis, it can be concluded that using an authoritative training style can improve “geri komi” kick technique.